Effect of Replacement of Maize by Animal Fat on Energy Utilization in Pigs - Elanchezhian, N; K, Ally (Indian Journal of Animal Nutrition, 2020)
The experiment was conducted to assess the effect of replacement of maize by different levels of animal fat on energy utilization in Large White Yorkshire (LWY) pigs. Thirty weaned piglets were randomly divided into three groups and were allotted to the three dietary treatments, T1 (control ration as per NRC, 1998), T2 (50 percent of maize of control ration replaced by animal fat) and T3 (100 percent of maize of control ration replaced by animal fat). A Digestibility trial was conducted following total collection method and gross energy was estimated using bomb calorimeter. Gross energy of feed and faeces were 4144.68, 4173.92, 4249.99 and 4102.04, 3834.24, 3453.09 kcal/kg, respectively for T1, T2 and T3 treatments. The apparent digestibility of GE was 85.85, 74.37 and 66.78 percent and the calculated digestible energy of feed was 3558.12, 3104.22 and 2837.90 kcal/kg, respectively for three treatments. The result of this experiment revealed that as the level of replacement of maize by animal fat increases, the efficiency of energy utilization was reduced in pigs fed isocaloric and isonitrogenous diet.